Exploring the Digital Healthcare Product’s Logistics and Mental Healthcare in the Metaverse: Role of Technology Anxiety and Metaverse Bandwidth Fluctuations - Pham Hoang An (iRASD Journal of Management)
This study is undertaken to investigate the effect of digital healthcare products’ logistics on mental healthcare in the metaverse along with taking into account the role of technology anxiety and metaverse bandwidth fluctuations. Due to the pressure brought on by serious diseases, growing healthcare costs, a rapidly ageing global population, insufficient labour elevated healthcare services, and scarce resources, it does not appear that the health system will be viable in the future. There is a need to be able to deliver health care from hospitals to our houses using cutting-edge technology rather than providing traditional health services using cutting-edge technology. The quantitative survey-based methodology has been used which indicates the targeted population as the staff in the healthcare sector. For this purpose, questionnaires were distributed among the targeted population and their response to 330 questionnaires out of 350 was evaluated using SPSS and AMOS. The results indicated a strong and significant relationship between digital healthcare products logistics and mental healthcare in the metaverse along with the significant moderation for both technology anxiety and metaverse bandwidth fluctuation. The management in various healthcare sectors is using digitalized approaches for carrying out the logistics. This has helped in reducing inefficiencies as well as improving accessibility. Senior managers in various healthcare sectors can keep track of the operations that are being carried out in the organization by using effective digital technologies. Such practices have revolutionized the healthcare system drastically. Other essential stakeholders, such as the patients, are also found to enjoy the benefits of the digital healthcare system as they have easy access to healthcare professionals as well as the required treatment and medicines contrary to the conventional healthcare system. For future studies, intrinsic factors such as motivation, as well as self-efficacy, could be taken as the mediating variables in the context of the current study for obtaining efficient results.